2022
DOI: 10.1002/cbin.11896
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis in cancer: The role of lipid signaling

Abstract: Malignantly transformed cells must alter their metabolic status to stay viable in a harsh microenvironment and maintain their ability to invade and spread. Anoikis, a specific detachment‐related form of apoptotic cell death, is a potential barrier to cancer cell metastasis. Several molecular/pathway alterations have been implicated in preventing anoikis in metastatic cancers. Specific alterations in the lipid metabolism machinery (such as an increase in fatty acid uptake and synthesis) and modifications in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 144 publications
0
21
0
Order By: Relevance
“…Disruption of cell-cell attachment or cell-ECM attachment leads to a form of apoptosis called “anoikis” ( Raeisi et al, 2022 ). This process can eliminate misaligned or shed cells under physiological or pathological conditions, contributing to the realization of tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of cell-cell attachment or cell-ECM attachment leads to a form of apoptosis called “anoikis” ( Raeisi et al, 2022 ). This process can eliminate misaligned or shed cells under physiological or pathological conditions, contributing to the realization of tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In many types of malignant tumors, meanwhile, we know that changes in carbohydrate metabolism, amino acid metabolism, and lipid metabolism mechanisms are associated with anoikis resistance, especially increased fatty acid uptake, and biosynthesis. [26] Likewise, at the initial stage of metastasis, malignantly transformed cells are easily killed by immune cells in the microenvironment, so malignant cells must transform their metabolic state to maintain their ability to metastasize and spread. In our risk score group, T cells gamma delta were distinguished to be the most crucial TICs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tumor cell resistance to anoikis determines its survival after detachment from the ECM, which is a prerequisite for malignant tumors to acquire invasive and metastatic colonization [7,8] . Therefore, anoikis may be a potential therapeutic treatment target for tumors [5] . Tumor cells can resist anoikis in the following ways: through autocrine growth factors or paracrine signaling by neighboring cells, resulting in activation of pro-survival signaling pathways; alteration of integrin expression patterns of integrins; and, reactive oxygen species (ROS)-mediated activation of growth factor receptors in a ligand-independent manner to escape apoptosis [9] and activation of epithelial-mesenchymal transition (EMT) [10] .…”
Section: Introductionmentioning
confidence: 99%